The effect of reading-concept mapping-reciprocal teaching on students’ communication skills - Sholihah, Mar'atus; Zubaidah, Siti; Mahanal, Susriyati; Listyorini, Dwi (Intelektual Pustaka Media Utama, 2025)
Communication skills are one of the abilities required for 21st-century learning. Students must consider communication skills in learning because they can guide students in conveying ideas effectively and interacting and collaborating with others. This study aimed to investigate the online reading-concept mapping-reciprocal teaching (REMAP-RT) learning model on students' oral and writing communication skills. The pretest-posttest control group design was employed in this study with three Biology Education study program classes at the State Islamic University in Tulungagung, Indonesia. This study included 89 students separated into three classrooms, each learning using one of three methods: i) REMAP-RT, ii) reciprocal teaching (RT), and iii) discussion-presentation. A questionnaire was used to assess students' oral and written communication skills. Analysis of covariance (ANCOVA) was used to compare differences in communication skills among the three treatment groups based on the questionnaire responses. The research findings revealed that students' oral and writing communication abilities improved across the board, with students in the REMAP-RT class showing the most substantial increase. This result of the research suggests that REMAP-RT improves students' oral and written communication skills in online learning.